(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Wave energy converters (WECs) have been used commonly in large-scale applications and are now included in several unmanned oceangoing vehicles. Wave energy is used to power propulsion systems and onboard instruments to increase deployment range and time, expanding the limits of ocean exploration. We describe the development and validation of a lumped parameter model representative of a small-scale WEC. This system can be useful for small marine systems and is motivated by Unmanned Underwater Vehicle (UUV) applications. Key components of the modeled heave-plate WEC include a surface element, a power take-off (PTO) and a negatively buoyant drag plate. The PTO is modeled as a mass-spring-damper and forces acting on the heave plate include nonlinear drag and added mass, forced by harmonic components. The surface element oscillates vertically in response to passing ocean waves, while the motion of the submerged heave plate is damped, resulting in a periodic differential in motion. As the surface float tends to pull the heave plate, an effectively tuned PTO captures this motion and efficiently converts it into electrical energy. The system is tuned for short period waves (1 to 6 sec) that are ubiquitous at moderate winds. Using the system model, the parameter space is explored under varying wave conditions, identifying optimal design configurations to maximize energy production. To validate the model, a physical prototype of the heave-plate generator was constructed and tested in a controlled experimental setting. The experimental apparatus features a linear actuator with an inline force sensor and component motion is assessed via video tracking. Results from these experiments provide critical insights into the performance of the PTO system under varying wave conditions, highlighting areas where the model aligns with and diverges from observed behavior. These findings informed iterative improvements to the model, enhancing its accuracy and reliability for future design iterations for an oceangoing WEC system.